2018
DOI: 10.1530/ec-17-0312
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of endoscopic vs microsurgical transsphenoidal resection for Cushing’s disease

Abstract: IntroductionIt is unclear whether the proportions of remission and the recurrence rates differ between endoscopic transsphenoidal surgery (TS) and microscopic TS in Cushing’s disease (CD); thus, we conducted a systematic review and meta-analysis to evaluate studies of endoscopic TS and microscopic TS.MethodsWe conducted a comprehensive search of PubMed to identify relevant studies. Remission and recurrence were used as outcome measures following surgical treatment of CD.ResultsA total of 24 cohort studies invo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
2
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 72 publications
(215 reference statements)
2
23
2
1
Order By: Relevance
“…Postoperative remission rates vary widely in the literature, depending on the adopted remission criteria, ranging from 65% to 93%. 15 In our study, no significant difference was observed in initial remission rate, remission rate after early second operation and overall remission between the two age groups.…”
Section: Discussioncontrasting
confidence: 59%
See 4 more Smart Citations
“…Postoperative remission rates vary widely in the literature, depending on the adopted remission criteria, ranging from 65% to 93%. 15 In our study, no significant difference was observed in initial remission rate, remission rate after early second operation and overall remission between the two age groups.…”
Section: Discussioncontrasting
confidence: 59%
“…Our data showed that the surgical remission rates were similar in both younger and older populations and that surgery remains safe and effective in older age group. Postoperative remission rates vary widely in the literature, depending on the adopted remission criteria, ranging from 65% to 93% . In our study, no significant difference was observed in initial remission rate, remission rate after early second operation and overall remission between the two age groups.…”
Section: Discussioncontrasting
confidence: 56%
See 3 more Smart Citations